'Next to godliness?' exploring cleanliness in peace and war. Issue 3 (3rd April 2019) - Mugglestone, Lynda
ABSTRACT: In the history of English, the early moral centring of cleanliness is conventionally depicted as having been eroded. This paper aims instead to explore its continued moral dynamism, using language as prime resource. Examining the complex semantic trajectories of cleanliness from Middle English onwards, it documents its shifting status in a number of disparate registers, including chastity, domestic virtue, and health, alongside the forms of moral expression these reveal. The conventionalised alliance of cleanliness with godliness forms part of this process of critical re-evaluation. The salience of cleanliness as moral device comes to the fore in a detailed study of language practice in the First World War. Across a range of discourse types, cleanliness is shown to retain potent moral and ideological force, not least in constructing both nationhood and enemy in a time of war.